2015
DOI: 10.1063/1.4913981
|View full text |Cite
|
Sign up to set email alerts
|

Start-up vortex flow past an accelerated flat plate

Abstract: Viscous flow past a finite flat plate moving in direction normal to itself is studied numerically.The plate moves with velocity $at^p$, where $p=0,0.5,1,2$. We present the evolution of vorticity profiles, streaklines and streamlines, and study the dependence on the acceleration parameter $p$. Four stages in the vortex evolution, as proposed by Luchini & Tognaccini (2002), are clearly identified. The initial stage, in which the vorticity consists solely of a Rayleigh boundary layer, is shown to last for a time-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…All our observations are consistent with the ones made by Xu and Nitsche 37 . However, we also observed the formation of secondary vortex structures emanating from the edges, seen in Figure 22(a4, c4), which was not reported in their study.…”
Section: Numerical Experimentssupporting
confidence: 93%
See 1 more Smart Citation
“…All our observations are consistent with the ones made by Xu and Nitsche 37 . However, we also observed the formation of secondary vortex structures emanating from the edges, seen in Figure 22(a4, c4), which was not reported in their study.…”
Section: Numerical Experimentssupporting
confidence: 93%
“…The computational setup for this flow is shown in Figure 9 along with the boundary conditions. For this flow setup, Reynolds number is defined as Re=l2νT, where l is the plate height, ν is the kinematic viscosity of the fluid, and T is a characteristic timescale defined by T=la12 for some constant a 37 …”
Section: Numerical Experimentsmentioning
confidence: 99%
“…However, the first three stages already occur within a small motion of the plate, i.e. within a travelled distance of 0.5-1 times the plate height (Xu & Nitsche 2015). Each of our experiments runs far into the fourth phase, which has not been investigated in great detail.…”
Section: Previous Work On Accelerating Platesmentioning
confidence: 92%
“…Previously, when this behaviour was observed during experiments by Lian & Huang (1989), the same observed flow behaviour was attributed to experimental defects. However, this behaviour being intrinsic to the flow was later disputed once again by Xu & Nitsche (2015), as they showed that by increasing the simulation resolution the instabilities disappear. However, Schneider et al (2014) report that the instabilities are affected by the shape of the plate tip which suggests that they are intrinsic to the flow.…”
Section: Previous Work On Accelerating Platesmentioning
confidence: 99%
See 1 more Smart Citation